A Review of Country Classification Frameworks in the Space Sector: Priorities, Limitations, and Global Considerations. (August 2022) - Oniosun, Temidayo Isaiah; Klinger, Julie Michelle
Abstract: The growth of space activities across the globe has led to various efforts to classify and rank countries according to their level of space sector development. This article reviews several classificatory frameworks published between 2008 and 2021. Each takes a different approach, but most center around a country's ability to own, operate and develop a specific set of technologies. This paper critically analyzes existing classification models, identifying their priorities and limitations. Finally, additional indicators that account for the diverse needs and interests of Global North and South countries and the rise of commercial space activities are introduced and discussed. Highlights: Article reviews existing country classification frameworks in the space sector. Existing country classification frameworks rely on a limited set of priorities. More diverse indicators are needed to appropriately classify countries in the space sector. Additional indicators that account for diverse needs and interests are introduced.